Pengukuran Kinerja Instansi Pemerintah dengan Pendekatan Balanced Scorecard - Giarti Pertiwi; Dian Imanina Burhany; Achmad Syarief (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to measure the performance of government agencies, National Land Agency of the Cimahi City Land Office using approach balanced scorecard. Performance measurement is carried out based on four perspectives: financial perspective, internal business process perspective, growth and learning perspective, and customer perspective. This type is descriptive qualitative research. The data sources used are primary and secondary data sources. Data collection using documentation and questionnaire methods. Documentation comes from the Performance Report of BPN Kantah Cimahi City, while the respondents come from employees of BPN Kantah Cimahi City. The results showed that the performance from a financial perspective was excellent for budget absorption, very efficient for efficiency ratios, and very effective for effectiveness ratios. Furthermore, the performance from the customer perspective is satisfactory, the internal business process perspective, and the learning and growth perspective is unsatisfactory. While the overall performance of BPK Kantah Cimahi City is unsatisfactory.